Transdermal STING Degradation Reprograms Innate‐Adaptive Immunity Crosstalk for Relapse‐Free Psoriasis and Comorbid Arthritis Therapy - Mengchao Ding; Zhenhai Pan; Ihsan Ullah; Ye Liu; Songke Shen; Mohamed E. El‐Khouly; Youyong Yuan (Advanced Functional Materials, 2026)
ABSTRACT Psoriasis is a chronic inflammatory disorder in which current therapies provide only transient symptomatic relief by suppressing pathogenic immune responses, while the restoration of immune homeostasis and prevention of relapse or comorbid arthritis remain unaddressed. Here, we present a microneedle‐based transdermal platform incorporating reactive oxygen species (ROS)‐responsive self‐immolative polymers (SIPs) to encapsulate a proteolysis‐targeting chimera (PROTAC) for selective degradation of stimulator of interferon genes (STING), a central regulator of innate immunity. Upon insertion into psoriatic skin, the SIPs are deposited into the dermis and undergo ROS‐triggered self‐immolation, releasing carbonyl sulfide, which is enzymatically converted into hydrogen sulfide (H 2 S), exerting local anti‐inflammatory and anti‐oxidant effects to relieve epidermal hyperplasia. Simultaneously, STING‐targeting PROTAC are internalized by dendritic cells and macrophages promoting targeted STING degradation and reprogramming the immune microenvironment. This dual mechanism suppresses innate immunity via M2 macrophage polarization and modulates adaptive responses by inducing tolerogenic dendritic cells to reducing skin‐resident memory T cells, thereby preventing epidermal hyperplasia and recurrence caused by immune stress. In imiquimod (IMQ)‐induced psoriasis, relapse, and psoriatic arthritis models, this strategy achieved durable remission and restored immune homeostasis, establishing a rationally engineered transdermal therapy for the long‐term management of psoriasis and its systemic complications.